2014
DOI: 10.3892/br.2014.297
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of microRNA in neurological disorders (Review)

Abstract: Abstract. MicroRNAs (miRNAs) are small, endogenous, non-coding RNA molecules that function as post-transcriptional regulators of gene expression by imperfect base-pairing with the 3'-untranslated regions of their target mRNAs. Altered expression of numerous miRNAs has been shown to be extensively involved in the pathogenesis of various diseases and cancers. Additionally, the specific expression of miRNAs in the nervous system has indicated that miRNAs are critical for the occurrence and development of neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 72 publications
2
37
0
Order By: Relevance
“…The role of miR223 in the brain has been investigated. miR-223 is expressed in the brain, regulates the differentiation of immature neurons[29], and exerts a neuroprotective role[30]. It was also reported that miR-223 is upregulated in PD and MSA compared to the controls [31].…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR223 in the brain has been investigated. miR-223 is expressed in the brain, regulates the differentiation of immature neurons[29], and exerts a neuroprotective role[30]. It was also reported that miR-223 is upregulated in PD and MSA compared to the controls [31].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are considered to play significant roles in many biologic processes, including cellular proliferation, differentiation, maturation, and apoptosis [4] . In addition, miRNAs have been implicated in the pathogenesis of common human diseases, such as cardiovascular [5] , neurologic [6] , and hematologic diseases, cancer [7] , and inflammatory and autoimmune diseases [8] . These research findings have led to new insights into IBD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, within 4 d following Dox administration, dTg-211 mice presented fourfold increases in the forebrain levels of miR-134 (Fig. 4F), known to be causally involved with the induction of convulsive seizures (7,10,11,47).…”
Section: Mir-211 Declinementioning
confidence: 99%
“…Also, miR-211 levels are elevated in epileptic human brain tissues (47), and epileptic events are arguably common in the AD brain (54). Therefore, the possibility of a miR-211 involvement in this condition should be explored.…”
Section: Mir-211 Excess Associates With Impaired Learning Strategy Inmentioning
confidence: 99%